Identification of Berberis spp. as Alternate Hosts for Puccinia achnatheri-sibirici Under Controlled Conditions and Morphologic Observations of Sexual Stage Development of the Rust Fungus - Ma, Xinyao; Liu, Yao; Li, Qiao; Tian, Xiaxia; Du, Zhimin; Kang, Zhensheng; Zhao, Jie (Frontiers in Microbiology, 2020)
Gramineous grasses are a large group of species, many of which act as accessory (secondary) host for a large number of rust fungi, including devastating rust pathogens of cereals. Among the rust fungi, some are known to be heteroecious and have a complete macrocyclic lifecycle with five types of spores on distinct plant species, but for many others the complete life cycle is unknown. Puccinia achnatheri-sibirici, a rust fungus infecting grasses in the genus Achnatherum, has been known for only its uredinial and telial stages, however the other (pycnial and aecial) stages has not been identified. In this study, we demonstrate that P. achnatheri-sibirici is a heteroecious, macrocyclic fungus with the sexual stage on barberry (Berberis spp.) through inoculation Pycnia and aecia were successively produced on the inoculated barberry plants. Inoculation of A. extremiorientale leaves with aeciospores produced yellow-orange uredinia with high infection types, whereas inoculation of wheat variety Mingxian 169, highly susceptible to Puccinia striiformis f. sp. tritici that causes stripe rust on wheat, produced chlorotic flecks but no uredinia. The ITS sequence analysis of P. achnatheri-sibirici did not match with any sequence in the NCBI database, and had the highest homology with 94% compared to P. brachypodii and P. aizazii. Observations of the uredinial, telial, and basidial stages on A. extremiorientale and pycnial and aecial stages on B. shensiana using light and scanning electron microscopes revealed its characteristics. Morphological characteristics of urediniospores and teliospores are most similar with those of P. achnatheri-sibirici describing in the literature. This study proved that (1) the life cycle of P. achnatheri-sibirici is heteroecious and macrocyclic and alternate host is barberry, (2) description of life stages in the sexual cycle, especially the morphologies of aecial, pycnial and basidial stages, and (3) expanding the knowledge of the rust flora on barberry.